Implications of climate change for sustainable agricultural production systems in ACP countries: Getting information and communication strategies right: compilation document - Sweetmore, Anne (Technical Centre for Agricultural and Rural Cooperation, 2009)
This publication provides a summary of a very busy week’s agenda, especially the media coverage, lessons from e-discussions, a summary of the main recommendations and conclusions of the seminar, and abstracts of the presentations...